IMPLEMENTASI HADIS SHAHIH MUSLIM NO. INDEKS 384 TERHADAP KESENIAN GEMBRUNGAN DI DESA KRANGGAN KECAMATAN GEGER KABUPATEN MADIUN - Silvi Nur Izzatul Aulia; Andris Nurita (Musnad : Jurnal Ilmu Hadis, 2023)
This article aims to find out how the implementation of the meaning of the hadith narrated by Imam Muslim towards the gembrungan art in Kranggan Village, Geger District, Madiun Regency. In modern times, the development of technology and culture has become increasingly sophisticated, so that in the end, the legacies of ancient ancestors are almost extinct. One of the legacies from ancient times is this gembrungan art. In this gembrungan art there are several moral values ​​that we can take as examples in everyday life. This gembrungan art is actually almost the same as hadroh and banjari in general. The reading that is read when doing gembrungan namely blessings on the Prophet SAW. In the hadith narrated by Imam Muslim, which will be studied at this time, it discusses the benefits of praying to the Prophet SAW. We as Muslims, namely the people of the Prophet Muhammad SAW, must routinely practice reciting blessings on the Prophet SAW, because in reading blessings there are many benefits, moreover reading one prayer can get 10 times the reward. To maintain the preservation of this art, the people of Kranggan Village, Geger District, Madiun Regency created a collection called this gembrungan art. Gradually, this art has developed again and is now recognized by the Regent of Madiun City. Do not forget also the function of this gembrungan art as a medium of propaganda through culture. Therefore, our current task is to maintain the preservation of this gembrungan art.